1988
DOI: 10.1152/ajpheart.1988.255.1.h7
|View full text |Cite
|
Sign up to set email alerts
|

Ionic basis of depressed automaticity and conduction by acetylcholine in rabbit AV node

Abstract: To investigate the ionic mechanisms underlying the negative chrono- and dromotropic effects of acetylcholine (ACh) on the atrioventricular (AV) node, experiments were carried out in rabbit AV node preparations with the use of double-microelectrode techniques. In current-clamp experiments (n = 6), 10(-6) M ACh hyperpolarized the resting membrane from -42.3 to -58.2 mV, decreased the specific membrane resistance from 2.54 to 1.27 k omega.cm2, decreased the space constant from 556 to 384 microns, and reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Subsequent investigations showed that ACh could also hyperpolarize membrane potential or stop spontaneous activity [Hiromasa et al, 1983;Nishimura et al, 1988]. Using voltage-clamp of small AVN preparations, Nishimura et al [1988] showed that ACh activated an inwardly rectifying potassium current (I KAch ) that altered passive as well as active membrane properties in a way that could account for the effects of ACh on the AVN. These authors also observed an effect of ACh on the slow inward current (I Ca,L ), which may augment the effect of activation of I KACh .…”
Section: Acetycholine-activated Potassium Current I Kachmentioning
confidence: 99%
“…Subsequent investigations showed that ACh could also hyperpolarize membrane potential or stop spontaneous activity [Hiromasa et al, 1983;Nishimura et al, 1988]. Using voltage-clamp of small AVN preparations, Nishimura et al [1988] showed that ACh activated an inwardly rectifying potassium current (I KAch ) that altered passive as well as active membrane properties in a way that could account for the effects of ACh on the AVN. These authors also observed an effect of ACh on the slow inward current (I Ca,L ), which may augment the effect of activation of I KACh .…”
Section: Acetycholine-activated Potassium Current I Kachmentioning
confidence: 99%
“…7 The mechanisms of action of acetylcholine on the AVN have been described elsewhere. 8,9 Limitations Although a short-acting muscarinic agonist was clearly a suitable drug for proof of concept for many reasons, this particular drug would be unsuitable for a long-term (pumpbased) clinical application. Acetylcholine is not very stable in solution, and the observed dose-response curves in the present study may be too steep (eg, the therapeutic window is too small).…”
Section: Sigg Et Al Focal Pharmacological Avn Modulation 2387mentioning
confidence: 99%
“…As características eletrofisiológicas de excitabilidade, condutividade e automatismo diferem entre o nódulo atrioventricular e o nódulo sinusal e entre os três tipos de células nodais 18,[21][22][23][24] . A acetilcolina, além de reduzir a velocidade de despolarização diastólica da corrente If, ativa diretamente uma corrente de saída composta pelo íon potássio denominada Ik.…”
Section: As Bases Iônicas Da Ativação Elétrica Do Coração Do Atletaunclassified